Advanced breeding strategies and future perspectives of salinity tolerance in rice - Haque, Md Azadul; Yusop, Mohd Rafii; Mohammad Yusoff, Martini; Syd Ali, Nusaibah; Yusuff, Oladosu; Datta, Debi Rani; Anisuzzaman, Mohammad; Ikbal, Mohammad Ferdous (Multidisciplinary Digital Publishing Institute, 2021)
Rice, generally classified as a typical glycophyte, often faces abiotic stresses such as excessive drought, high salinity, prolonged submergence, cold, and temperature, which significantly affects growth, development, and ultimately, grain yield. Among these negative impacts of abiotic factors in rice production, salinity stress is a major constraint, followed by drought. There is considerable research on the use of marker-assisted selection (MAS), genome editing techniques, and transgenic studies that have profoundly improved the present-day rice breeders’ toolboxes for developing salt-tolerant varieties. Salinity stresses significantly affect rice plants during seedling and reproductive stages. Hence, greater understanding and manipulation of genetic architecture in developing salt-tolerant rice varieties will significantly impact sustainable rice production. Rice plants’ susceptibility or tolerance to high salinity has been reported to be the result of coordinated actions of multiple stress-responsive quantitative trait loci (QTLs)/genes. This paper reviews recent literature, updating the effects of salinity stress on rice plants and germplasm collections and screening for salinity tolerance by different breeding techniques. Mapping and identification of QTLs salt tolerance genes are illuminated. The present review updates recent breeding for improvement in rice tolerance to salinity stress and how state-of-the-art tools such as MAS or genetic engineering and genome editing techniques, including mutagenesis and conventional breeding techniques, can assist in transferring salt-tolerant QTLs genes into elite rice genotypes, accelerating breeding of salt-resistant rice cultivars.